2021
DOI: 10.1101/2021.10.01.462769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical loading and hyperosmolarity as a daily resetting cue for skeletal circadian clocks

Abstract: In mammals, temporally coordinated daily rhythms of behaviour and physiology are generated by a multi-oscillatory circadian system, entrained through cyclic environmental cues (e.g. light). Presence of niche-dependent physiological time cues has been proposed, which would allow local tissues flexibility of adopting a different phase relationship if circumstances require. Up till now, such tissue-unique stimuli have remained elusive. Here we show that cycles of mechanical loading and osmotic stimuli within phys… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The results further align with the understanding that a hyper‐osmotic change mimics the in vivo osmotic environment resulting from tissue compression. Interestingly, a hyper‐osmotic change was further shown to mediate the circadian cycle in IVD cells, which highlights the extent to which a cyclic osmotic environment may influence cellular biology 36 . However, our results do contrast with findings from a porcine organ culture model, which demonstrated that a simulated diurnal osmotic cycle (430 mOsm/kgH 2 O for 8 h and 550 mOsm/kgH 2 O for 16 h) 37 reduced sGAG accumulation compared to a static 430 mOsm/kgH 2 O.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results further align with the understanding that a hyper‐osmotic change mimics the in vivo osmotic environment resulting from tissue compression. Interestingly, a hyper‐osmotic change was further shown to mediate the circadian cycle in IVD cells, which highlights the extent to which a cyclic osmotic environment may influence cellular biology 36 . However, our results do contrast with findings from a porcine organ culture model, which demonstrated that a simulated diurnal osmotic cycle (430 mOsm/kgH 2 O for 8 h and 550 mOsm/kgH 2 O for 16 h) 37 reduced sGAG accumulation compared to a static 430 mOsm/kgH 2 O.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, a hyper‐osmotic change was further shown to mediate the circadian cycle in IVD cells, which highlights the extent to which a cyclic osmotic environment may influence cellular biology. 36 However, our results do contrast with findings from a porcine organ culture model, which demonstrated that a simulated diurnal osmotic cycle (430 mOsm/kgH 2 O for 8 h and 550 mOsm/kgH 2 O for 16 h) 37 reduced sGAG accumulation compared to a static 430 mOsm/kgH 2 O. Part of the discrepancy may be explained by the different species tested, the scale at which the osmotic conditions were applied (i.e., organ culture vs. cells), and the method through which the solutions were osmotically adjusted (i.e., NaCl vs. sucrose).…”
Section: Discussionmentioning
confidence: 99%
“… 41 While several ion channels are expressed in chondrocytes that regulate calcium signalling, 42 TRPV4 and PIEZOs are two of the most relevant ion channels in chondrocytes in this context, both have been shown to improve cartilage and bone formation, and by mediating the anabolic effects of mechanical loading. 43 However, extracellular calcium and membrane calcium channels were not found to be involved in hyperosmolarity‐induced clock resetting in mouse cartilage, 44 and the mTORC2‐AKT‐GSK3β pathway is hypothesised to act as a convergent mechanism mediating clock entrainment elicited by mechanical loading and hyperosmolarity. 44 Nevertheless, specific pathways activated upon different external stimuli may be dependent on a number of factors such as the exact nature of the stimuli and the differentiation phase of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…While several ion channels are expressed in chondrocytes that regulate calcium signalling 40 , TRPV4 and PIEZOs are two of the most relevant ion channels in chondrocytes in this context, both have been shown to improve cartilage and bone formation, and by mediating the anabolic effects of mechanical loading 41 . However, extracellular calcium and membrane calcium channels were not found to be involved in hyperosmolarity-induced clock resetting in mouse cartilage 42 , and the mTORC2-AKT-GSK3β pathway is hypothesised to act as a convergent mechanism mediating clock entrainment elicited by mechanical loading and hyperosmolarity 42 . Nevertheless, specific pathways activated upon different external stimuli may be dependent on a number of factors such as the exact nature of the stimuli and the differentiation phase of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…However, extracellular calcium and membrane calcium channels were not found to be involved in hyperosmolarity-induced clock resetting in mouse cartilage 42 , and the mTORC2-AKT-GSK3β pathway is hypothesised to act as a convergent mechanism mediating clock entrainment elicited by mechanical loading and hyperosmolarity 42 . Nevertheless, specific pathways activated upon different external stimuli may be dependent on a number of factors such as the exact nature of the stimuli and the differentiation phase of the cell.…”
Section: Discussionmentioning
confidence: 99%